Tingkat Kapasitas Pembudidaya Ikan dalam Mengelola Usaha Akuakultur secara Berkelanjutan - Fatchiya, Anna (Jurnal Penyuluhan, 2015)
This study was undertaken to identify fish farmer characteristic and supporting institutional, and to know the degree of fish farmer capacity to manage of aquabusiness sustainability. This was done by carrying out a survey involving random sample of 278 fish farmers from Bogor and Cianjur Districts of West Java Province. Both descriptive statistic and independent-samples T-test were used in analysing the data generated from the resesarch. Result presented showed that majority of fish farmers were low on formal education, non-formal education, business experience, family size, income, and business scale, but age was moderate. The supporting of institutional showed that support of financial institutional was low, input production institutional and marketing institutional was high, and information institutional was moderate. Performance of extension worker was low, and supporting of fish farmer group was high. Capacity of fish farmer as follows to practice of business function was moderate, to solve a problem was low, to plan of business and to adapt it to change of environment was high.Key words: capacity, fish farmer, aquabusiness, sustainability